The Effects of Glucomannan Hydrolysates and BV Gel on Nugent Score, Treg Cell Percentage, and TGF-? level in Bacterial Vaginosis - Retnoningrum, Ambar Dwi; Nurseta, Tatit; Prawiro, Sumarno Reto; Endharti, Agustina Tri; Wahyuni, Endang Sri (Indonesian Journal of Medicine, 2018)
Background: Bacterial vaginosis is commonly experienced by women of reproductive age. The Nugent score is the gold standard for diagnosing bacterial vaginosis. Prebiotic Glucomannan hydrolysates (GMH) as a therapy in the treatment of bacterial vaginosis and has an immunomodulatory effect on the immune system and provides cellular immunity. The purpose of this study was to examine the effects of GMH and BV Gel on Nugent scores, Treg cell presentation, and TGF ? levels in bacterial vaginosis of women of childbearing age.Subjects and Method: This was an experimental study. A sample of 24 women aged 20 to 45 years old with bacterial vaginosis (Nugent score ?7) was divided into 4 groups: oral antibiotic group metronidazole (500mg), combination of GMH (300mg) and metronidazole, 5 ml BV Gel tube, and combination of GMH and BV Gel scores. The dependent variables were GMH and BV Gel administrations. The independent variables Nugent score, Treg presentation, and TGF-? level. Nugent score, Treg cell presentation, and TGF ? level were measured on day-0, day-11, and day-22. The data were analyzed by one way Anova.Results: The results of the analysis after treatment on day 22 showed that the GMH and BV gel were able to reduce Nugent scores, increase Treg cell presentation and TGF ? levels in bacterial vaginosis of women of childbearing age.Conclusion: GMH as an alternative therapy for bacterial vaginosis compared with antibiotic treatment can improve normal vaginal flora and stimulate the immune system in vitro and in vivo significantly.Keywords: Glucomannan Hydrolysates, BV Gel, Nugent sel Treg score, TGF ?Correspondence:Ambar Dwi Retnoningrum. Masters Program of Midwifery, Universitas Brawijaya, Malang, East Java. Email: adreambar@gmail.com. Mobile: +6281335743696.Indonesian Journal of Medicine (2018), 3(1): 33-43https://doi.org/10.26911/theijmed.2018.03.01.05